Corals in a Changing World - Duque Beltran, Carmenza; Tello Camacho, Edisson (IntechOpen, 2018)
Corals comprise a wide variety of colonial marine invertebrates belonging to the Phylum Cnidaria. Their polyps form the most colorful, complete, and diverse communities on the Earth resembling underwater cities, commonly called coral reefs, which host a wide variety of invertebrates and fish species. They are highly productive ecosystems, contribute to the health of the biosphere, and offer a good number of economic and ecological services to coastal populations and to many people around the world. However, due to a diverse number of natural and anthropogenic stressors, corals have shown a severe decline over the past few decades. Being aware of the importance and relevance of the facts described, the book "Corals in a Changing World" offers new scientific information regarding the actual status and, in some cases, the resilience state of coral reef systems. Timely information is critical for managers and decision makers to implement sustainable management measures according to the ecological condition of coral reefs. In addition, the book also discusses the use of well-maintained coral microcosms to provide a good basis for performing experiments with natural fluctuations and to present studies dedicated to the coral diversity characterization and to their importance as a source of important biological compounds, which could be converted into industrial products.